Targeting Metastatic Colorectal Cancer with Immune Oncological Therapies - Galbraith, Norman J. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Colorectal cancer that has become metastatic continues to have a poor outlook. Many patients will undergo intensive chemotherapy, often with limited effects but many side effects. In other types of cancer, immunotherapy has shown to be effective by targeting the immune cells of the patient and restoring their function to fight off cancer. This review explores the up-to-date evidence for immunotherapy in metastatic colorectal cancer. We have discussed in which patients this treatment is effective, but also why this has not been effective in a large number of patients. By summarizing the key components of the immune cells within the proximity to the tumour and its areas of spread, we discuss how these components can be targeted. Areas of future research are also highlighted, which includes combining immunotherapy with current treatments, such as surgery, radiotherapy and chemotherapy as well as some recent advances from basic and translational studies that promises to improve outcomes in these patients. ABSTRACT: Metastatic colorectal cancer carries poor prognosis, and current therapeutic regimes convey limited improvements in survival and high rates of detrimental side effects in patients that may not stand to benefit. Immunotherapy has revolutionised cancer treatment by restoring antitumoural mechanisms. However, the efficacy in metastatic colorectal cancer, is limited. A literature search was performed using Pubmed (Medline), Web of Knowledge, and Embase. Search terms included combinations of immunotherapy and metastatic colorectal cancer, primarily focusing on clinical trials in humans. Analysis of these studies included status of MMR/MSS, presence of combination strategies, and disease control rate and median overall survival. Evidence shows that immune checkpoint inhibitors, such as anti-PD1 and anti-PD-L1, show efficacy in less than 10% of patients with microsatellite stable, MMR proficient colorectal cancer. In the small subset of patients with microsatellite unstable, MMR deficient cancers, response rates were 40–50%. Combination strategies with immunotherapy are under investigation but have not yet restored antitumoural mechanisms to permit durable disease regression. Immunotherapy provides the potential to offer additional strategies to established chemotherapeutic regimes in metastatic colorectal cancer. Further research needs to establish which adjuncts to immune checkpoint inhibition can unpick resistance, and better predict which patients are likely to respond to individualised therapies to not just improve response rates but to temper unwarranted side effects.